(untitled) (International Conference on Educational Discoveries and Humanities, 2025)
This article examines the linguistic and cultural features of phrases expressing the concept education in English and Uzbek languages. The research aims to identify semantic, structural, and cultural differences and similarities between educational expressions in both languages. Through contrastive analysis, the study reveals that while both languages share universal values related to learning, diligence, and intelligence, their linguistic realizations are shaped by different cultural traditions and historical contexts. The findings contribute to understanding how national mentality influences language use in the field of education.